Die karakter van die kerk in perspektief van huidige teologiese besinning - Potgieter, P. C. (Verbum et ecclesia, 1990)
The character of the church - a perspective on current theological thought The role of the church in society is currently much focused upon in theological thought. The author analyses various characteristics of the church with reference to views of well known theologians. As community of faith it is the body of Christ revealed very visibly in the world representing the kingdom of God. For that very reason the idea of a national church is unacceptable. The church is one, catholic and apostolic community, even particularly in its visible form. Though Scripture gives no clear guidelines on the structure of the church, there are many general biblical norms to be considered in ecclesiastical law and government.